Puheen analyysin perusteet: Oppitunti 6 - Lennes, Mietta (2021)
In this lesson, you get familiar with the basic use of the ELAN tool in speech research. You learn some good practices in speech transcription work and you notice why it can pay to transcribe conversation recordings by aligning the transcriptions with the corresponding time spans in the original media file. You can perform efficient queries and searches even in a large speech corpus, if it has been annotated in a suitable, sturctured way. Finally, you try out some of the search facilities that are built in ELAN and you learn about regular expressions that can be very useful when studying annotated speech or text corpora.
Keywords: fonetiikka; transkriptio (fonetiikka); litterointi; kielentutkimus; viittomakieli; video; ääni (ihmisääni); keskustelu; keskustelunanalyysi; puheentutkimus; puheen analyysi; multimedia; leksikografia; säännölliset lausekkeet; annotointi